AtGCS promoter-driven clustered regularly interspaced short palindromic repeats/Cas9 highly efficiently generates homozygous/biallelic mutations in the transformed roots by Agrobacterium rhizogenes–mediated transformation - Liu, Shuang; Wang, Xiuyuan; Li, Qianqian; Peng, Wentao; Zhang, Zunmian; Chu, Pengfei; Guo, Shangjing; Fan, Yinglun; Lyu, Shanhua (Frontiers in Plant Science, 2022)
Agrobacterium rhizogenes–mediated (ARM) transformation is an efficient and powerful tool to generate transgenic roots to study root-related biology. For loss-of-function studies, transgenic-root-induced indel mutations by CRISPR/Cas9 only with homozygous/biallelic mutagenesis can exhibit mutant phenotype(s) (excluding recessive traits). However, a low frequency of homozygous mutants was produced by a constitutive promoter to drive Cas9 expression. Here, we identified a highly efficient Arabidopsis thaliana gamma-glutamylcysteine synthetase promoter, termed AtGCSpro, with strong activity in the region where the root meristem will initiate and in the whole roots in broad eudicots species. AtGCSpro achieved higher homozygous/biallelic mutation efficiency than the most widely used CaMV 35S promoter in driving Cas9 expression in soybean, Lotus japonicus, and tomato roots. Using the pAtGCSpro-Cas9 system, the average homozygous/biallelic mutation frequency is 1.7-fold and 8.3-fold higher than the p2 × 35Spro-Cas9 system for single and two target site(s) in the genome, respectively. Our results demonstrate the advantage of the pAtGCSpro-Cas9 system used in ARM transformation, especially its great potential in diploids with multiple-copy genes targeted mutations and polyploid plants with multiplex genome editing. AtGCSpro is conservatively active in various eudicots species, suggesting that AtGCSpro might be applied in a wide range of dicots species.